The Administrative Wage and Labor Market Flow Panel - Stefan Seth; Heiko Stüber (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2018)
This paper describes the updated version of the Administrative Wage and Labor Market Flow Panel (AWFP, v1.1). The AWFP is a dataset on labor market flows and stocks for the universe of German establishments covering the years 1975–2014. It contains data on job flows, worker flows, and wages for each establishment. The AWFP contains these information also for parti-tions of the labor force according to various employee characteristics and for some subgroups of employees. The AWFP is available on the annual and quarterly frequency.
Keywords: 330; establishment data; job flows; worker flows; wages; German administrative data